Urban Sufism: Membangun Kecerdasan Spiritual Masyarakat Perkotaan Era Modern Melalui Pendekatan Transpersonal - Musbihin, Aziz; Khatimah, Khusnul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to explore the role of Sufism in building the spiritual intelligence of urban communities in the modern era. With increasing urbanization and the pressures of modern life, there is an urgent need to strengthen the dimension of spirituality in the urban context. Sufism, as a branch within Islam that emphasizes developing an individual's relationship with God through introspection and meditation, is emerging as a promising approach in meeting this need. This research will use a qualitative approach by conducting a literature review of relevant works in the fields of Urban Sufism, spiritual intelligence, and urban life. The sources used include books, journals, articles, and related academic writings. Thematic analysis will be used to identify key themes emerging in the relevant literature. The results of this study get three points, namely: Awakening of Spirituality and the Phenomenon of Urban Sufism, Spiritual Intelligence in Transpersonal Psychology and Efforts to Increase Spiritual Intelligence in Urban Sufism.